Endocrine disrupting chemicals research program of the U.S. Environmental Protection Agency: summary of a peer-review report. - Harding AK; Daston GP; Boyd GR; Lucier GW; Safe SH; Stewart J; Tillitt DE; Van Der Kraak G (Environmental Health Perspectives, 2006)
At the request of the U.S. Environmental Protection Agency (EPA) Office of Research and Development, a subcommittee of the Board of Scientific Counselors Executive Committee conducted an independent and open peer review of the Endocrine Disrupting Chemicals Research Program (EDC Research Program) of the U.S. EPA. The subcommittee was charged with reviewing the design, relevance, progress, scientific leadership, and resources of the program. The subcommittee found that the long-term goals and science questions in the EDC Program are appropriate and represent an understandable and solid framework for setting research priorities, representing a combination of problem-driven and core research. Long-term goal (LTG) 1, dealing with the underlying science surrounding endocrine disruptors, provides a solid scientific foundation for conducting risk assessments and making risk management decisions. LTG 2, dealing with defining the extent of the impact of endocrine-disrupting chemicals (EDCs) , has shown greater progress on ecologic effects of EDCs compared with that on human health effects. LTG 3, which involves support of the Endocrine Disruptor Screening and Testing Program of the U.S. EPA, has two mammalian tests already through a validation program and soon available for use. Despite good progress, we recommend that the U.S. EPA a) strengthen their expertise in wildlife toxicology, b) expedite validation of the Endocrine Disruptors Screening and Testing Advisory Committee tests, c) continue dependable funding for the EDC Research Program, d) take a leadership role in the application of 'omics' technologies to address many of the science questions critical for evaluating environmental and human health effects of EDCs, and e) continue to sponsor multidisciplinary intramural research and interagency collaborations.